(untitled) (Research, Society and Development, 2021)
The Assessment is characterized as an instrument capable of defining the student’s learning conditions and their relationship with teaching. Thus, the assessment of learning by students with disabilities should have the same function that it has for other students: being formative, procedural, mediating, investigative and inherent to the pedagogical process. In this way, we list as general objective: To analyze the types of existing conceptions about school evaluation in the researches submitted to Revista Brasileira de Educação Especial. For this we have defined the following specific objectives: identify how researchers perceive school evaluation in special education and the prevailing educational paradigms; characterize the type of school evaluation present in the writings of researchers in the period 2006-2020 and understand how research on school evaluation is being developed for the target audience of Special Education in an inclusive perspective. This research has a qualitative approach, and of an exploratory and bibliographic methodological nature. The interstice selected for the Study of Art refers to the year 2006 to 2020, the justification is due to a period in which all published numbers are available in the Scielo virtual library. In this period of fifteen years, 61 editions were launched, and these have made our corpus of analysis. 594 surveys were identified that dealt with special education in a general context, by reaffirming the search for evaluation in special education, we delimit our research corpus with a catalog of 26 surveys. We identify the preference in evaluations that do not contemplate the educational scope.